Determination of relation between the quaternary sediments and land use dissemination on the basis of Šventoji river basin - Litvinaitis, Andrius; Bagdžiūnaitė-Litvinaitienė, Lina; Šaučiūnas, Laurynas (International Conference “Environmental Engineering”, 2017)
On preparing of the first management plans of River Basin Districts have been found that diffuse agricultural pollution is one of the most important causing factor and the most significant impact on the quality of water bodies. Diffuse agricultural pollution can be from 45% to 80% of nitrate nitrogen pollution load of water bodies. Pollution is transported by water surface and subsurface runoff through sediments from agricultural territories. This article aims at evaluating of relation between the Quaternary sediments and Land use dissemination. The lithological factor (sandy, loamy, argillaceous) of the basin was calculated based on Quaternary map of Lithuania M 1:200000 and Lithuanian river map M 1:50000. The land-use factor of the basin was calculated based on Corine Land cover M 1:100000 using ArcGis software. In order to carry out more thorough analysis of the determination of relation between the Quaternary sediments and Land use dissemination in given territories, sections of 0–50 m, 50–200 m, 200–500 m, 500–800 m, 800–1000 m and >1000 m were established, calculating the distance in meters from the riverbank.